Resequencing PNMT in European hypertensive and normotensive individuals: no common susceptibilily variants for hypertension and purifying selection on intron 1 - Viigimaa Margus; Ots Mai; Kozich Viktor; Juhanson Peeter; Kepp Katrin; Laan Maris (BMC, 2007)
Abstract Background Human linkage and animal QTL studies have indicated the contribution of genes on Chr17 into blood pressure regulation. One candidate gene is PNMT, coding for phenylethanolamine-N-methyltransferase, catalyzing the synthesis of epinephrine from norepinephrine. Methods Fine-scale variation of PNMT was screened by resequencing hypertensive (n = 50) and normotensive (n = 50) individuals from two European populations (Estonians and Czechs). The resulting polymorphism data were analyzed by statistical genetics methods using Genepop 3.4, PHASE 2.1 and DnaSP 4.0 software programs. In silico prediction of transcription factor binding sites for intron 1 was performed with MatInspector 2.2 software. Results PNMT was characterized by minimum variation and excess of rare SNPs in both normo- and hypertensive individuals. None of the SNPs showed significant differences in allelic frequencies among population samples, as well as between screened hypertensives and normotensives. In the joint case-control analysis of the Estonian and the Czech samples, hypertension patients had a significant excess of heterozygotes for two promoter region polymorphisms (SNP-184; SNP-390). The identified variation pattern of PNMT reflects the effect of purifying selection consistent with an important role of PNMT-synthesized epinephrine in the regulation of cardiovascular and metabolic functions, and as a CNS neurotransmitter. A striking feature is the lack of intronic variation. In silico analysis of PNMT intron 1 confirmed the presence of a human-specific putative Glucocorticoid Responsive Element (GRE), inserted by Alu-mediated transfer. Further analysis of intron 1 supported the possible existence of a full Glucocorticoid Responsive Unit (GRU) predicted to consist of multiple gene regulatory elements known to cooperate with GRE in driving transcription. The role of these elements in regulating PNMT expression patterns and thus determining the dynamics of the synthesis of epinephrine is still to be studied. Conclusion We suggest that the differences in PNMT expression between normotensives and hypertensives are not determined by the polymorphisms in this gene, but rather by the interplay of gene expression regulators, which may vary among individuals. Understanding the determinants of PNMT expression may assist in developing PNMT inhibitors as potential novel therapeutics.